PENGARUH PER, DER, ROA, CR TERHADAP RETURN SAHAM (STUDI KASUS PERUSAHAAN MANUFAKTUR SUB-SEKTOR TEKSTIL DAN GARMEN YANG TERDAFTAR DI BEI TAHUN 2018-2022) - Amrullah, Hasanal Mahardhika; Sumekar, Kertati; Rahayu, Tina (Jurnal Studi Manajemen Bisnis, 2024)
This study aims to determine the effect price earning ratio, debt-to-equity ratio, return on assets, Â current ratio on stock retur. The objects chosen in this study were textile and garment companies listed on the Indonesia Stock Exchange from 2018 to 2022. This research is a descriptive study with a quantitative approach. The sample selection using purposive sampling which yielded 58 samples. This study uses secondary data. The data analysis method used is Descriptive Statistics, Classical Assumption Test, Hypothesis Test, Multiple Linear Regression Analysis. The results showed that: (1) price earning ratio does not affect the stock return, (2) debt-to-equity ratio ratio does not affect the stock return, (3) return on assets does positive and significant influence the stock return, (4) current ratio does negative and significant influence the stock return, (5) price earning ratio, debt-to-equity ratio, return on assets, and current ratio simultaneously positive and significant affect the Stock Return.